INFLUENCE OF TAX MORALITY AND TAX CULTURE ON TAX COMPLIANCE - Ihenyen Confidence Joel; Epekele Wisdom; Kojo Precious Bolouimbelemoere (ZILLZELL MEDIA PRIMA, 2023)
This research explored the influence of tax morality and tax culture on tax compliance in Nigeria. The primary objective is to examine the relationships among tax morality, tax culture, and tax submission. The research utilized a survey design with a sample size of 384 participants selected through purposive sampling from the working population of Bayelsa State, Nigeria. Data was collected using a structured questionnaire, which included sections for personal data and research hypotheses. Inferential statistics, particularly regression analysis, were employed to analyze the data. The outcomes of the regression reveal a substantial impact of tax morality and tax culture on tax submission in Nigeria. The high R-squared value of 0.719 indicates that approximately 71.9% of the variability in tax compliance can be attributed to the combined effects of tax morality and tax culture. This underscores the importance of these factors in shaping taxpayers' willingness to adhere to tax regulations, even after considering other potential predictors. The adjusted R2 of 0.515 implies that tax morality and tax culture continue to exert a notable influence, independent of other variables. Furthermore, the statistical significance of the F-statistic (13.003) and its connected p-value (0.002) reaffirm the robustness of the model, indicating that either tax morality or tax culture, or both, significantly affect tax compliance. To foster tax compliance, the study recommends comprehensive taxpayer education, the promotion of a positive tax culture, and recognition of tax-compliant individuals and organizations.